Poesia infanto-juvenil brasileira contemporânea (2008-2012) - Sampaio, Ana Paula de Almeida Santos (2014)
This essay aims to carry out a study of contemporary Brazilian youth and children's poetry produced between 2008 and 2012 which is focused on the youth and children's audience, in order to identify features such as the thematic, formal structure, illustrations, and also to make their authors and illustrators known. To achieve this objective, the essay presents theoretical review of poetry as genre and the history of children's literature, looking for aesthetic traits in the analyzed books. As a theoretical basis we used the authors Cara (1985), Culler (1999), Soares (2007), Staloni (2003), among others, to discuss about the lyrical genre and the authors Coelho (2002), Zilberman (2011) and Lajolo (2011) for the discussion about children's poetry. For the development of the essay, twenty books were selected from catalogs of publishing houses that publish youth and children's poetry, observing the criterion of originality. The analysis encompassed the following aspects: materiality, which comprises all material elements of elaboration of the book; the formal structure of the poems, the thematic and the illustrations. The results showed that the contemporary youth and children's poetry is a verbal and visual poetry, a combination between text and image. Most of the illustrations are not merely an adornment to the text, they confirm the significance of the text. The theme is diverse: love, daily life, the search for identity, disappointment, family, everything that involves captivation or appeal to youth and children's audience; the formal structure shows freedom of layout creation, free verse, but without eliminating some elements of the classic models. The authors and illustrators are mostly young, of southern and southeastern of Brazil and male; many still unconsecrated by their involvement with literature and who reconcile their careers of writer and illustrator with the ones of journalist, university professor, musician, among others. The materiality associated with the verbal group helps the composition of a unique artistic object, since it presents itself in a creative, humorous and engaging way, contributing to the building of the genre and its constitution as an aesthetic object. When evaluating contemporary youth and children's poetry, the research allowed the appreciation in the academic scene and, therefore, within the literate circuit, poets, illustrators and contemporary poetry, drawing on specific themes of youth world with mastery and aesthetic quality can greatly contribute to the formation of readers if known by reading mediators and reach to the young readers.